On the scientific status of economic policy: A tale of alternative paradigms - Giorgio Fagiolo; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
In the last years, a number of contributions has argued that monetary - and, more generally, economic - policy is finally becoming more of a science. According to these authors, policy rules implemented by central banks are nowadays well supported by a theoretical framework (the New Neoclassical Synthesis) upon which a general consensus has emerged in the economic profession. In other words, scientific discussion on economic policy seems to be ultimately confined to either fine-tuning this consensus model, or assessing the extent to which elements of art still exist in the conduct of monetary policy. In this paper, we present a substantially opposite view, rooted in a critical discussion of the theoretical, empirical and political-economy pitfalls of the neoclassical approach to policy analysis. Our discussion indicates that we are still far from building a science of economic policy. We suggest that a more fruitful research avenue to pursue is to explore alternative theoretical paradigms, which can escape the strong theoretical requirements of neoclassical models (e.g., equilibrium, rationality, etc.). We briefly introduce one of the most successful alternative research projects - known in the literature as agent-based computational economics (ACE) - and we present the way it has been applied to policy analysis issues. We conclude by discussing the methodological status of ACE, as well as the (many) problems it raises.
Keywords: 330; Economic Policy; Monetary Policy; New Neoclassical Synthesis; New Keynesian Models; DSGE Models; Agent-Based Computational Economics; Agent-Based Models; Post-Walrasian Macroeconomics; Evolutionary Economics; Wirtschaftspolitik; Geldpolitik; Regelbindung; Neue Neoklassische Synthese; Neukeynesianische Makroökonomik; Dynamisches Gleichgewicht; Agentenbasierte Modellierung; Theorie